If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n = 9 + -1(3n + -7) Reorder the terms: 5n = 9 + -1(-7 + 3n) 5n = 9 + (-7 * -1 + 3n * -1) 5n = 9 + (7 + -3n) Combine like terms: 9 + 7 = 16 5n = 16 + -3n Solving 5n = 16 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 5n + 3n = 16 + -3n + 3n Combine like terms: 5n + 3n = 8n 8n = 16 + -3n + 3n Combine like terms: -3n + 3n = 0 8n = 16 + 0 8n = 16 Divide each side by '8'. n = 2 Simplifying n = 2
| 14w^3=15w | | x-5=2x/3 | | iz^4=-1 | | 5x-x+y= | | (x+y)=(y+x) | | y*(x*z)=(y*x)*z | | 3w-(9-w)=3 | | z(y+x)=zy+zx | | z*x=x*z | | -3(3n+6)=3 | | x2-25/3x | | 2x-4(4x-13)=220 | | 12=4x+4(2x-18) | | 1/3x=x-4 | | f=-sin^8(10x^5-22) | | (6t-1)=3(t-1)+6 | | 2z^2+4iz-2=0 | | j-s+z=2 | | 7p+6=54-p | | 6x+7(3x-10)=119 | | 3m+5=5(6-m) | | 3r+3=17r+5 | | Z^4-4z^3+9z^2-10z+6=0 | | f=(x^3-6x)(9x^4+2x^2-12) | | 4+6x=3(2x+2) | | 102-(5x+12)=5(x+7)+x | | 44=4x+4(x-5) | | 44=4x+4(2x-18) | | f(x)=5x^3+7x^2-9x | | 5y-8+y+36=6y+30-2y | | 5x-4(2x-8)=-1 | | 6r+4=41r+9 |